Empowering women and other marginalized groups in agrifood supply chains: Targeted investments drive inclusion in Honduras and India - Wiegel, Jenny; Elias, Marlene; Soto Joya, Fernanda; Shijagurumayum, Meghajit (2025)
The Alliance of Bioversity and CIAT’s evidence-based approach has enabled two agribusinesses in Honduras to design and implement gender-responsive strategies, improving women’s empowerment and social inclusion, thus fostering more equitable coffee supply chains. In India, the Ethical Tea Partnership (ETP), a global membership-based organization, used the approach to deepen its understanding of the diverse women involved in the smallholder tea sector and the conditions of their engagement in the supply chain.